Management of Transposed Arteriovenous Fistula Swing Point Stenosis at the Basilic Vein Angle of Transposition by Stent Grafts. Issue 6 (November 2017) - Nassar, George M.; Beathard, Gerald; Rhee, Edward; Khan, Abdul Jabbar; Nguyen, Binh
Introduction: Transposed basilic vein arteriovenous fistulas suffer from stenosis at their basilic angle of transposition (BAT). This lesion exhibits frequent recurrence after angioplasty. The primary goal of this study was to determine the effect of stent-graft placement on BAT lesion- and access-patency. The secondary goals were to determine the frequency of intervention pre- and post-stent placement and stent-associated stenosis. Methods: Thirty-seven cases had stent-grafts placed at their BAT to manage stenosis. Cases served as their own controls by analyzing their lesion- and access-patency pre- and post-stent placement. Student's t-test was used for analysis of continuous variables. Categorical variables were evaluated by Fisher's exact test. Tests were considered significant when p was ≤0.05. Results: At 6 and 12 months, pre-stent lesion primary patency rates were 29% and 3%, and post-stent were 57% and 40%, respectively. Lesion primary assisted patency rates were 39% and 13%, and post-stent were 91% and 80%, respectively. At 6 and 12 months, pre-stent access primary patency rates were 29% and 3%, and post-stent were 26% and 19%, respectively. Pre-stent primary access assisted patency rates were 36% and 10%, and post-stent were 82% and 75%, respectively. Lesion intervention rates averaged 0.47/month pre-stent and 0.13/month post-stent. Access intervention rate averaged 0.50/month pre-stent, and 0.15/month post-stent. Stent-associated stenosis was seen in 23 cases. Conclusions: Treatment of BAT stenosis with stent-grafts had positive impact on the target lesion and the dialysis access circuit.